Innovation In Financing Boarding School Equipment Through The Cash Waqf Scheme At Sharia Financial Institutions - Adzikra Rajuli; Dewi Lestari; Ahmad Azzam Nouvaldi (Universitas Darunnajah, 2025)
The purpose of this study was to analyze the potential for optimizing cash waqf as a productive source of financing to support the fulfillment of equipment needs for new students in Islamic boarding schools. Islamic boarding school-based Islamic financial institutions have a great opportunity to collect waqf funds directly from their members, whose backgrounds include teachers, employees, students, parents of students, and the community around the Islamic boarding school. This study uses a qualitative descriptive design with a case study to describe the management of cash waqf at the Amanah Gontory Sejahtera Shariah Cooperative. The research data consists of primary data from observations and secondary data from literature on waqf, cash waqf, and Islamic boarding school cooperatives. Data analysis was carried out through reduction, presentation, and drawing conclusions. The analysis refers to the Miles and Huberman Theory (data display, data interpretation, and conclusion drawing). The results of the study indicate that a cash waqf scheme managed productively for the procurement of equipment for new students has the potential to be implemented provided that management is carried out transparently, professionally, and accountably. This research provides recommendations for a cash waqf management model that can be replicated by other Islamic boarding schools as a strategy for waqf-based economic empowerment. Thus, cash waqf can be a crucial instrument for supporting sustainable financial independence in Islamic boarding schools.